P46 Vascular adhesion protein-1 promotes inflammation and fibrogenesis in murine steatohepatitis. (16th November 2010) - Claridge, L C; Weston, C J; Haughton, E L; Westerlund, N; Lalor, P F; Smith, D J; Adams, D H
Abstract : Introduction: VAP-1 is an adhesion molecule which promotes lymphocyte recruitment to the liver. It is released in a soluble form (sVAP-1) from adipose tissue and the hepatic vascular bed. sVAP-1 has insulin-like effects, can initiate and propagate oxidative stress and is implicated in vascular complications of the metabolic syndrome. Our group has discovered that VAP-1 is expressed and secreted by hepatic stellate cells and we have reported that serum sVAP-1levelsareelevated in NAFLD and predict fibrosis. These observations suggest that VAP-1 may have a role in mediating interactions between lymphocytes and stromal cells to promote inflammation induced fibrosis in NAFLD. Aim: To investigate a possible pathogenic role for VAP-1 in NAFLD by determining the effects of the inhibition or absence of VAP-1 in murine models of steatohepatitis. Method: 1. A high fat diet (HFD) was administered for 18 weeks in wild type (WT) C57Bl/6 mice (n=5) and VAP-1 null mice (n=5). 2. A methionine choline deficient (MCD) diet was administered for 6 weeks in WT mice (n=6), WT mice receiving an anti-VAP-1 antibody (n=6) and VAP-1 null mice (n=6). Results: In the HFD model VAP-1 null mice developed less steatosis on quantitative analysis of Oil Red O staining (p<0.001) and had fewer inflammatory foci (p<0.05) than WT mice. They were also protected against the onset of fibrosis with less collagen deposition (p<0.001) and lower levels of hepatic gene expression of SMA (p<0.05) and collagen 1, α 1 (p<0.05). In the MCD model VAP-1 null and antibody treated mice were equally protected from liver injury; showing less steatosis (p<0.001), fewer inflammatory foci (p<0.001), less collagen staining (p<0.001) and lower hepatic SMA (p<0.001) and collagen type 1, α 1 (p<0.01) mRNA expression than WT mice. Both models of steatohepatitis resulted in increased hepatic gene expression of VAP-1 when compared with age sex matched mice on normal diet. Conclusion: ElevatedsVAP-1 levels in NAFLD and increased hepatic VAP-1 expression in murine steatohepatitis suggest a role for VAP-1 in the pathogenesis of NAFLD. Inhibition and/or absence of VAP-1 are protective in two murine models of steatohepatitis implicating an important role for VAP-1 in hepatic fibrogenesis and suggesting it may be a potential therapeutic target in NAFLD.